Activity of Aspargate (Cathepsin D), Cysteine Proteases (Cathepsins B, B + L, and H), and Matrix Metallopeptidase (Collagenase) and their influence on protein and water-holding capacity of muscle in commercially farmed Atlantic halibut ( Hippoglossus hippoglossuss L.). - Johnston, Ian Alistair; Solberg, C; Johnston, I A (Journal of Agricultural and Food Chemistry, 2008)
Atlantic halibut (Hippoglossus hippoglossus L.) were commercially farmed in Helgeland, Norway (May 2004-May 2005). The average weight (Mb) of fish increased over the 12 month production cycle by similar to 73% for females and similar to 50% for males, although during the winter months (November-early May) Mb was unchanged in females and declined by 18% in males because of sexual maturation and sperm release. Periods of zero or negative growth were associated with up to 5.7% (females) and 17.9% (males) decline in fast muscle protein content. The activities of cathepsins B, B + L, H, and D showed a reciprocal relationship and were highly correlated with the changes in protein content. Water-holding capacity was measured as the liquid loss increased from 3-5% in November to 11-13% in May. Two general additive models (GAMs) showed that cathepsin B + L, cathepsin D, and collagenase explained 73.1% of the total variance in protein content, while cathepsin H was the largest contributor to liquid loss, explaining similar to 48.8% of the total variance. The results indicate that to obtain the best flesh quality Atlantic halibut should be harvested in the fall or early winter when the liquid loss and cathepsin activities are low and less likely to cause problems during secondary processing and storage.